2019
DOI: 10.1186/s12882-018-1181-1
|View full text |Cite
|
Sign up to set email alerts
|

Successful re-administration of Pazopanib in a patient with metastatic renal cell carcinoma and a history of Pazopanib-induced nephrotic syndrome: a case report

Abstract: BackgroundDrug-induced nephrotic syndrome (NS) can be resolved by eliminating the causative agents. However, patients with metastatic cancer have not been previously reported to achieve complete recovery from anticancer drug-induced NS after discontinuation of treatment, because many patients die of cancer progression before NS is restored.Case presentationA 67-year-old man presented with edema of both lower extremities. He received pazopanib therapy for recurrent metastatic renal cell carcinoma (mRCC) for 17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 9 publications
1
46
2
Order By: Relevance
“… 31–40 Although the underlining mechanism is yet to be fully elucidated, previous epidemiological studies revealed that a lower level of handgrip strength was associated with all-cause mortality, 33–35 40 chronic diseases 39 and cardiovascular mortality. 38 40 However, we did not observe an association between handgrip strength and mortality in our study population. This may be due to the high level of handgrip strength among Olympic athletes.…”
Section: Discussioncontrasting
confidence: 72%
“… 31–40 Although the underlining mechanism is yet to be fully elucidated, previous epidemiological studies revealed that a lower level of handgrip strength was associated with all-cause mortality, 33–35 40 chronic diseases 39 and cardiovascular mortality. 38 40 However, we did not observe an association between handgrip strength and mortality in our study population. This may be due to the high level of handgrip strength among Olympic athletes.…”
Section: Discussioncontrasting
confidence: 72%
“…Some studies also suggest that the localization of AVF in hemodialyzed patients may be associated with symptoms severity, which in turn influences the QOL [24]. These observations, however, were made in a cohort of dialyzed patients and it remains unclear whether they can be extrapolated from KTRs with persistent AVF.…”
Section: Plos Onementioning
confidence: 99%
“…The antihypertensive effects of propolis have been studied in different animal models (see Table 4 ) and have been attributed to several biological activities, including the modulation of vascular tone, anti-inflammatory and antioxidant [ 88 ].…”
Section: Cardiovascular Effects Of Propolismentioning
confidence: 99%
“…A double-blind, placebo-controlled study demonstrated that the administration of Beepolis ® (Laboratorio Rotterdam Ltda, San Javier, Chile), a 3% Chilean Propolis solution in propylene glycol, decreased BP in hypertensive patients over a period of 90 days [ 93 ]. However, in another double-blind, placebo-controlled study, the co-administration of Brazilian Green Propolis (500 mg/day) and antihypertensive drugs to patients with hypertension and chronic kidney disease showed no change in BP after a period of 12 months [ 88 ].…”
Section: Cardiovascular Effects Of Propolismentioning
confidence: 99%